Reconstruction of the anterior wall of the frontal sinus using bovine bone matrix: histological study with monkeys - Magro Filho, Osvaldo [UNESP]; Marão, Heloisa Fonseca; Queiroz, Thallita Pereira; Silva, Pedro Ivo dos Santos; Reis, Robson Henrique; Garcia Júnior, Idelmo Rangel [UNESP] (My University, 2011)
The purpose of this study was to evaluate the repair process in the reconstruction of the anterior wall of the frontal sinus of monkeys with bovine bone matrix. Four adult Cebus apella monkeys underwent an ostectomy of the anterior wall of the frontal sinus. The frontal sinus mucosa and the nasofrontal duct were not manipulated. Reconstruction occurred with implants of bovine bone matrix laminae measuring 2.0 x 2.5 cm and 0.4 mm thick, stabilized under pressure in the lateral wall of the frontal sinus. The monkeys were sacrificed over a period of 150 days and routine laboratory procedures were followed for hematoxylin-eosin staining and histologic evaluation of the specimens. Neoformed bone tissue was observed in contact with the frontal sinus mucosa and the bovine bone matrix. The frontal sinus mucosa remained whole without fibrous tissue or cystic formations. There was no occurrence of cellularization as well as revascularization of the bovine bone matrix, though it has permitted bone conduction on this surface. It was possible to conclude that the demineralized bovine bone matrix was biotolerable, being incorporated into the bone without the presence of inflammatory cells with characteristics of inertness and antigenicity and behaved as an osteoconductive material.
Keywords: Reconstruction; Frontal sinus; Bone matrix